Molecular detection of Anaplasma species in dogs in Colombia - Vargas-Hernandez,Giovanni (2016)
Abstract Anaplasma platys and A. phagocytophilum are tick-borne pathogens that parasitize platelets and neutrophils, respectively, of humans and animals. The former is the etiological agent of canine cyclic thrombocytopenia, while the latter is that of canine granulocytic anaplasmosis. This work involved the detection and identification of Anaplasma species in blood samples from dogs in Colombia, using molecular techniques. Between December 2008 and April 2009, blood samples were drawn from the cephalic vein of 91 dogs in the central-western region of Colombia (cities of Bogota, Villavicencio and Bucaramanga) and stored in tubes containing EDTA. These samples were used in 16S rRNA-Anaplasma spp. nPCR and the preparation of blood smears. One (1.1%) of the 91 sampled dogs showed inclusions suggestive of Anaplasmataceae agents in the cytoplasm of platelets. Based on PCR followed by sequencing and phylogenetic analysis, A. platys and Anaplasma sp. closed related to A. phagocytophilum were detected in two and one dog, respectively. Interestingly, all the samples were negative for specific msp-2-A. phagocytophilum real-time qPCR, suggesting the circulation of an Anaplasma species phylogenetically related to A. phagocytophilum in dogs in the aforementioned region. Hence, Anaplasma spp. circulates among dogs in Colombia, albeit with low frequency. To the best of authors' knowledge, this is the first molecular detection of Anaplasma spp. in dogs in Colombia.